2005
DOI: 10.1051/vetres:2004047
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of hepatic infiltrates and hepatic lymph nodes of lambs primarily and challenge infected with Fasciola hepatica, with and without triclabendazole treatment

Abstract: -The phenotype of the hepatic inflammatory infiltrate and hepatic lymph nodes (HLN) was analysed in lambs primarily and challenge infected with Fasciola hepatica. Group 1 was primarily and challenge infected with two doses of 200 metacercariae (mc) each and was nontreated. Trickle infection was administered to five groups: group 2 was challenge infected and nontreated; group 3 was primarily infected and non-treated; group 4 was primarily infected and treated with triclabendazole (TCBZ) at 12 weeks postinfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
(41 reference statements)
1
6
0
1
Order By: Relevance
“…Using this marker, it was established that the proportion of CD4 + T cells in the local lymph nodes of ITT sheep did not alter significantly in response to Fasciola infection. This is in agreement with previous studies showing that the progressive increase in HLN weight and cell number after Fasciola infection was accompanied by a disproportionate increase in B cells (33,34). The contrasting cytokine profiles between F. hepatica ‐ (susceptible) and F. gigantica‐ (resistant) infected ITT sheep at 3 weeks p.i.…”
Section: Discussionsupporting
confidence: 94%
“…Using this marker, it was established that the proportion of CD4 + T cells in the local lymph nodes of ITT sheep did not alter significantly in response to Fasciola infection. This is in agreement with previous studies showing that the progressive increase in HLN weight and cell number after Fasciola infection was accompanied by a disproportionate increase in B cells (33,34). The contrasting cytokine profiles between F. hepatica ‐ (susceptible) and F. gigantica‐ (resistant) infected ITT sheep at 3 weeks p.i.…”
Section: Discussionsupporting
confidence: 94%
“…Fasciolosis control is almost exclusively carried out by strategic applications of a wide number of effective anthelmintics (Sanchez-Andrade et al 2001). Only triclabendazole is efficacious against both pre-adults in hepatic parenchyma and adults in the bile ducts (Boray et al 1983;Perez et al 2005). However, the effectiveness of triclabendazole represents problems of resistance (Fairweather and Boray 1999;Robinson et al 2002;Fairweather 2005;Fairweather 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cornelissen et al (2001), were able to detect positive animals by egg count only from week 9 in sheep and even later in cattle from week 15 onwards after natural infection of animals with F. hepatica, and Arias et al (2005), in their experimental work have detected positive animals through fecal examination 11 weeks after primary infection. Perez et al (2005), reported that eggs in stools indicates the presence of mature adult flukes in the bile ducts and gallbladder, but a period longer than 10 weeks after infection is required so most of the pathological damage has already occurred. The classification of liver pathology and the level of Fasciola infestation within the herd were compared based on postmortem findings of liver lesions and antibody detection by ELISA, the results of light and sever infection were similar, 23% and 2% of the animals were lightly and severely infected respectively, in both tests.…”
Section: Discussionmentioning
confidence: 99%